Pengaruh Pengetahuan Investasi Dan Literasi Keuangan Terhadap Minat Berinvestasi Di Pasar Modal Dengan Perkembangan Teknologi Digital Sebagai Variabel Moderasi - Muthia Willi Amanda; Mondra Neldi; Putri Azizi (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
This research aims to determine the influence of Investment Knowledge and Financial Literacy on Investment Interest in the Capital Market with the Development of Digital Technology as a Moderating Variable. The population of this study is students of the Faculty of Economics and Business, Universitas Putra Indonesia "YPTK" Padang. The sampling technique used is Simple Random Sampling with a sample of 100 students. Data collection techniques used a questionnaire and analyzed the data using Multiple Regression Analysis through the SPSS 25 application program. The results of the study indicate that Investment Knowledge and Financial Literacy have a significant effect on Investment Interest in the Capital Market with the Development of Digital Technology moderating the relationship between Investment Knowledge, Financial Literacy, and Investment Interest in the Capital Market. The Contribution of Investment Knowledge and Financial Literacy is 52.8%, and the Contribution of Investment Knowledge, Financial Literacy, and Development of Digital Technology is 54.3%.